2016
DOI: 10.1158/1940-6207.capr-15-0348
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Associated Alterations in Inflammation, Epigenetics, and Mammary Tumor Growth Persist in Formerly Obese Mice

Abstract: Using a murine model of basal-like breast cancer, we tested the hypothesis that chronic obesity, an established breast cancer risk and progression factor in women, induces mammary gland epigenetic reprogramming and increases mammary tumor growth. Moreover, we assessed whether the obesity-induced epigenetic and protumor effects are reversed by weight normalization. Ovariectomized female C57BL/6 mice were fed a control diet or diet-induced obesity (DIO) regimen for 17 weeks, resulting in a normal weight or obese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 33 publications
4
38
0
2
Order By: Relevance
“…Metformin, extensively used for treatment of type 2 diabetes mellitus, has already been shown, at low dose, to be safe and reduce recurrence of colorectal adenoma in nondiabetic patients following initial polyp resection . Because obesity‐promoted cancers have been shown in some cases to involve epigenetic changes , other potential opportunities for chemoprevention in young adults include the use of epigenetic targeted therapies .…”
Section: Disrupting the Linkage Between Obesity And Young Adult Cancersmentioning
confidence: 99%
“…Metformin, extensively used for treatment of type 2 diabetes mellitus, has already been shown, at low dose, to be safe and reduce recurrence of colorectal adenoma in nondiabetic patients following initial polyp resection . Because obesity‐promoted cancers have been shown in some cases to involve epigenetic changes , other potential opportunities for chemoprevention in young adults include the use of epigenetic targeted therapies .…”
Section: Disrupting the Linkage Between Obesity And Young Adult Cancersmentioning
confidence: 99%
“…Though currently there are no data supporting the benefit of lifestyle habits in improving BC outcomes [7]. However, there are ongoing trials (e.g.…”
Section: Targetable Pathways In the Clinicmentioning
confidence: 99%
“…We and others have shown that obesity can induce aberrant DNA methylation of genes involved in growth factor and inflammatory signaling (29, 40). To assess whether the energy balance-dependent effects on ERα and ERβ expression are controlled epigenetically, we characterized epigenetic alterations in mammary tissue DNA from baseline mice, from CR and OW mice after 5 months on diet, and from survival study mice after 14 to 22 months of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Library preparation and sequencing for baseline, CR and OW in the 5-month time point and survival study were performed at UT MD Anderson Cancer Center’s DNA Methylation Analysis Core and Science Park Next-Generation Sequencing Facility, according to published protocols as previously described (29) (Supplementary Table S1). Samples from DIO mice were not analyzed given the cost of RRBS and the similarities between OW and DIO mice in ERα and ERβ mRNA and protein expression.…”
Section: Methodsmentioning
confidence: 99%